Modeling evidence for large, ENSO-driven interannual wintertime AMOC variability - K L Smith; L M Polvani (Environmental Research Letters, 2021)
Recently established North Atlantic ocean observing arrays, such as RAPID/MOCHA, have revealed a large degree of high-frequency variability in the Atlantic Meridional Overturning Circulation (AMOC). Climate modeling studies of the AMOC, however, have traditionally focused on the low-frequency variability of the annual mean AMOC, with an emphasis on multi-decadal and longer time-scale variability. Thus, little is known about the sources of interannual wintertime, wind-driven AMOC variability. Analyzing the Community Earth System Model, we here show the existence of a robust leading mode of interannual variability in the wintertime AMOC that is distinct from the leading mode of the annual mean. We further show that this mode of variability is significantly linked to the El Niño-Southern Oscillation via the North Atlantic Oscillation.